The application of intellectual property rights to the processing of haminjon resin into perfume products - Sagala, Wilson; Anggusti, Martono (Priviet Social Sciences Journal, 2025)
This article discusses the application of Intellectual Property Rights (IPR), especially patent protection, to the results of processing haminjon sap into perfume products as a form of innovation based on local wisdom. Haminjon sap, a non-timber forest product typical of North Sumatra, has high economic potential if processed into value-added products, such as perfume. However, the protection of this innovation still faces various legal and practical obstacles. Based on Law Number 13 of 2016 concerning Patents, every invention that meets the elements of novelty, inventive steps, and can be applied in industry is entitled to legal protection. However, the implementation of this protection in the small business sector is still limited due to low IPR literacy, minimal access to information, and relatively high patent registration costs for small businesses. This condition causes many small business actors to not understand the importance of exclusive rights to their inventions, thereby risking losing ownership rights and the economic value of the results of their innovations. Therefore, efforts are needed to increase legal awareness, technical assistance, and affirmative policies from the government to facilitate access to patent protection for local products such as perfume made from haminjon sap, so that they can compete sustainably in the national and international markets.